2020
DOI: 10.1007/s12145-019-00427-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of flight altitude and cover orientation on Digital Surface Model (DSM) accuracy for flood damage assessment in Murcia (Spain) using a fixed-wing UAV

Abstract: Soil erosion, rapid geomorphological change and vegetation degradation are major threats to the human and natural environment. Unmanned Aerial Systems (UAS) can be used as tools to provide detailed and accurate estimations of landscape change. The effect of flight strategy on the accuracy of UAS image data products, typically a digital surface model (DSM) and orthophoto, is unknown. Herein different flying altitudes (126-235 m) and area coverage orientations (N-S and SW-NE) are assessed in a semi-arid and medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…In addition, UAV Remote Sensing (UAV-RS) is being gradually achieved by employing UAVs as carriers with imaging or non-imaging sensors to capture high-resolution remote sensing images, SAR images, as well as highprecision laser point clouds [1][2][3]. Since low-altitude and small UAVs exhibit several advantages (e.g., mobility, flexibility, low-cost, and rich data results) [4], they have been Sensors 2021, 21, 8109 2 of 17 adopted to generate 3D scenes by integrating Structure from Motion (SfM) and Multi-View Stereo (MVS) algorithms [5] for landslide disaster monitoring [6], flood hazard assessment [7], geomorphological evolution analysis [8], as well as crop monitoring [9].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, UAV Remote Sensing (UAV-RS) is being gradually achieved by employing UAVs as carriers with imaging or non-imaging sensors to capture high-resolution remote sensing images, SAR images, as well as highprecision laser point clouds [1][2][3]. Since low-altitude and small UAVs exhibit several advantages (e.g., mobility, flexibility, low-cost, and rich data results) [4], they have been Sensors 2021, 21, 8109 2 of 17 adopted to generate 3D scenes by integrating Structure from Motion (SfM) and Multi-View Stereo (MVS) algorithms [5] for landslide disaster monitoring [6], flood hazard assessment [7], geomorphological evolution analysis [8], as well as crop monitoring [9].…”
Section: Introductionmentioning
confidence: 99%
“…While there is a clear tradeoff in product resolution with flight altitude (see Table 2), vertical accuracy does not demonstrate a clear trend with altitude. A similar study using a consumer-grade UAS to survey a shrubland area revealed an increase in vertical error with altitude (altitude range: 126-235 m) at the first site and consistent vertical error across altitudes at the second site (Anders et al, 2020). The range of low altitudes (25-120 m) used in this study are those most commonly used by United States UAS pilots given that flight altitudes above 120 m are restricted by the Federal Aviation Administration (FAA).…”
Section: Vertical Errormentioning
confidence: 77%
“…Very low-altitude UAV flight generates images with a very high spatial resolution; however, this results in limited area coverage and a safety problem. Very high altitude UAV flight reduces the spatial resolution and is likely to lose important information [24,25]. Therefore, these images were captured at an altitude of about 20 m to enable the ground resolution is about 1.3 cm/pixel, providing appropriate spatial information for yellow rust disease detection.…”
Section: Uav Multispectral Imaging Systemmentioning
confidence: 99%